APLIKASI PENILAIAN KINERJA DOSEN BERBASIS ANDROID - Iwan Lesmana; Dede Irawan (NUANSA INFORMATIKA, 2018)
Lecturer's evaluation is a way to know the influence of lecturers' teaching on the students, the assessment process of the teaching preparation, the learning material, the teaching material presentation, the lecturer competence, the class management and the evaluation of the learning. in addition to the assessment of the students, the assessment of lecturers conducted study program is considered important to see the performance of lecturers. In this study build an application to evaluate or assess the performance of lecturers. In this research the method used is RAD (Rapid Application Development) due to the preparation of the application only takes about 6 months and for the development of the system megunakan UML (Unified Modeling language). Application of this application there are two methods of access is through smatphone android and desktop for administrator and Study Program level. While the research was conducted at the University of KuninganKeywords: Lecturer Evaluation, RAD, UML, Smartphone, Android, Universitas Kuningan